HUBUNGAN ANTARA HIGIENE PERORANGAN, KONDISI JAMBAN KELUARGA DAN INFORMASI YANG DITERIMA DENGAN KEJADIAN DEMAM TIFOID DI WILAYAH KERJA PUSKESMAS NOGOSARI BOYOLALI - Agung Triono; Heru Subaris Kasjono; Anisa Catur Wijayanti (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2016)
Backgroud: Typhoid fever is a disease caused by infection with the bacterium Salmonella typhi, the disease is still a public health problem, especially in developing countries.Objective: The purpose of this study was to analyze the relationship between personal hygiene, conditions of household toilets and information received by the incidence of typhoid fever in Puskesmas Nogosari Boyolali. Methods:This type of research was observational research with case control design. Population of cases in this study were all patients with typhoid fever in January-December 2015, while population control is not the typhoid fever patients. Selection of the sample in the case group of 35 people and control as many as 35 people were done using Fixed Disease Sampling techniques while using a statistical test Chi Square test.Results: The results of this study indicate that there is a relationship between the habit of washing hands after defecation (p = 0.008; OR = 3.750; 95% CI = 1.383 to 10.169), there is a relationship between the habit of washing hands before eating (p = 0.030; OR = 2.909; 95% CI = 1.093 to 7.739), there is a relationship between eating habits outside the home (p = 0.039; OR = 3.000; 95% CI = 1.034 to 8.702), there is a correlation between the received information with the incidence of typhoid fever (p = 0.007; OR = 4.008; 95% CI = 1.428 to 11.247) and there is no relationship between the habit of washing raw food that will be eaten immediately (p = 0.225), family latrine condition (0.220) and the incidence of typhoid fever in Puskesmas Nogosari Boyolali.Key Words: Information, Personal hygiene, Toilet condition, Typhoid Fever